2023
DOI: 10.1002/adom.202300213
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Absorption and Refraction Properties of V4C3 MXene and its Use for an Ultra‐Broadband Saturable Absorber

Abstract: Large optical nonlinearity at short‐wavelength‐infrared (SWIR) has enabled 2D MXene to be used explosively in ultrafast nonlinear photonics and optoelectronics. Despite the high technological interest in V4C3 MXene in electrochemistry, investigations from a nonlinear photonics perspective have yet to be conducted. Here, the nonlinear optical characteristics of V4C3 MXene at SWIR wavelengths are systemically investigated. First, Z‐scan measurements are performed and the saturated absorption and self‐defocusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…Based on their robust chemical, electronic, and nonlinear optical properties, MXenes have been widely utilized in electrochemistry and optoelectronics. 38,39 To date, enormous efforts have been paid to exploit MXene in nonlinear photonics for SAs at short-wave infrared (SWIR) wavelengths, including Ti 3 C 2 T x , 40 Ti 3 CNT x , 41 V 2 C, 42 V 4 C 3 , 43 Mo 2 C, 44 Ta 4 C 3 , 45 and Nb 2 C. 46 Nb 4 C 3 is part of the MXene family, which was first fabricated from the Nb 4 AlC 3 MAX phase by Gogotsi et al in 2013. 47 Nb 4 C 3 started to be utilized in electrochemistry after Zhao et al reported a higher capacity of Nb 4 C 3 compared with that of titanium carbide MXene.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their robust chemical, electronic, and nonlinear optical properties, MXenes have been widely utilized in electrochemistry and optoelectronics. 38,39 To date, enormous efforts have been paid to exploit MXene in nonlinear photonics for SAs at short-wave infrared (SWIR) wavelengths, including Ti 3 C 2 T x , 40 Ti 3 CNT x , 41 V 2 C, 42 V 4 C 3 , 43 Mo 2 C, 44 Ta 4 C 3 , 45 and Nb 2 C. 46 Nb 4 C 3 is part of the MXene family, which was first fabricated from the Nb 4 AlC 3 MAX phase by Gogotsi et al in 2013. 47 Nb 4 C 3 started to be utilized in electrochemistry after Zhao et al reported a higher capacity of Nb 4 C 3 compared with that of titanium carbide MXene.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of MXenes has reignited interest in the investigation of MAX phases. The number of known MAX phases to date exceeds 70, and nearly 100 MXene materials can be obtained by varying the composition or ratio of the M and X layer elements. MAX phases and MXenes with different structures and properties open the door for applications in various fields. …”
Section: Introductionmentioning
confidence: 99%
“…However, compared with unitary and binary system 2D materials, ternary system materials have received increasing attention due to the advantages of containing a large number of compounds and tunable physical properties through stoichiometry variations. 33,34…”
Section: Introductionmentioning
confidence: 99%